Human-Computer Interaction, Tourism and Cultural Heritage First International Workshop, HCITOCH 2010, Brescello, Italy, September 7-8, 2010. Revised Selected Papers - Cipolla Ficarra, Francisco V.; Castro Lozano, Carlos; Nicol, Emma.; Kratky, Andreas; Cipolla-Ficarra, Miguel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Workshop on Human-Computer Interaction, Tourism and Cultural Heritage, HCITOCH 2010, held in Brescello, Italy, in September 2010. The 17 revised papers presented were carefully reviewed and selected from numerous submissions. Providing strategies for a creative future with computer science, quality design and communicability, the papers discuss the latest advances in the areas of augmented realities, computer art, computer graphics, e-commerce, eco-design, emerging technologies, dynamic and static media (2D & 3D), HCI, interactive systems, mixed reality, networking, simulation languages, tourism, usability, video games, virtual classroom and virtual museum.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computers and Society